An Analysis of Figurative Language in the Poem My Mistress Eyes Are Nothing Like the Sun - Muhammad, Muhaimin (English Literature Studi Program Universitas Islam Makassar, 2024)
This research aims to analyze and interpret the types of figurative language used in the poem My Mistress' Eyes Are Nothing Like the Sun. The study addresses the research problem of identifying dominant figurative language types and their interpretive methods, focusing on their contribution to understanding the poem’s meaning. Using Knickerbocker and Renninger's (1963) theory to classify figurative language types and Charles W. Kreidler's (1998) framework for interpreting language, the study applied qualitative content analysis. The findings reveal five types of figurative language in the poem: simile, hyperbole, metaphor, irony, and allusion. Among these, simile, hyperbole, irony, and allusion each appeared in two lines (14%), while metaphor was the least frequent, appearing in one line (8%). Notably, 36% of the poem contains literal language without figurative expressions. Regarding interpretive methods, connotation was the most frequently used (27%), followed by reference and denotation (21% each). Less common methods include lexical grammatical meanings (16%), morphemes (5%), homonymy and polysemy (5%), and lexical ambiguity (5%). This study highlights the predominance of similes and connotations in shaping the poem's meaning, contributing to a nuanced appreciation of its moral and literary value. The findings underscore the utility of combining linguistic and literary approaches to deepen the analysis of figurative language in poetry, offering valuable insights for literary studies and moral value analysis in literature.